(3TQM bUjOI CfhGY GdeLGRs - (3CMeO Hf Ydj GdefLhQs; (3CHhYHO Gddg eMeO Hf CMeO Hf GdUHGZ GdLPGejs
(3ChdgG (B:s
(3GdMeO ddg Mb MeOg hHYO Ydi bUjOI CfhGY YdGbGJ GdeLGR ddEeGe GdYdGeI Hf GdUHGZ GdecfGSi hGdbUjOI gPg jG SGFdkG MVQ GdYdGeGJ GdJi hVY GdeLGR HgG jShZ hjMed s
(3BNQgG (B:s
(3hHRjGOI HdGZJg YdjgG hGdebGe jbJVi RjGOI GdHdGZI hHdRheI ddMbjbI hESJdRGeg EjGgG hQGLY eG JbOe hHGddg JYGdi GdJhajb s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B1s
(3GdfSNI HgG MhGTs
(3JHUQI GdYfhGf (B:s
(3TQMs
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG CQVg s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdeLGejYs